2017
DOI: 10.3389/fnhum.2017.00395
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Gray Matter Volume in the Social Brain Network in Adults with Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by behavioral impairment in social interactions. Although theoretical and empirical evidence suggests that impairment in the social brain network could be the neural underpinnings of ASD, previous structural magnetic resonance imaging (MRI) studies in adults with ASD have not provided clear support for this, possibly due to confounding factors, such as language impairments. To further explore this issue, we acquired structural MRI da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 111 publications
(150 reference statements)
6
48
2
1
Order By: Relevance
“…The opposite direction of the alteration of the caudate nucleus in autism has also previously been found (43). This is not the case for the IFG and OFG, which showed lower densities in autism in our study, where prior studies found mixed results (44,45). Importantly, the brain regions identified by our analyses have earlier been implicated in the neurobiology and/or neurocognition of autism.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The opposite direction of the alteration of the caudate nucleus in autism has also previously been found (43). This is not the case for the IFG and OFG, which showed lower densities in autism in our study, where prior studies found mixed results (44,45). Importantly, the brain regions identified by our analyses have earlier been implicated in the neurobiology and/or neurocognition of autism.…”
Section: Discussioncontrasting
confidence: 55%
“…Importantly, the brain regions identified by our analyses have earlier been implicated in the neurobiology and/or neurocognition of autism. In IC10, structural and/or functional alterations of the insula, IFG, and OFC have been associated with social and non-social cognitive impairments in autism (45)(46)(47)(48). A meta-analysis reported abnormal functional activations of the insula, IFG, and OFG during social cognition tasks in autism (49).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these two regions was further solidified in another study, identifying both frontal and temporal lobe volumes as most discriminative of ASD (Katuwal et al, 2015). Additionally, reduced GMV was observed in the parietal lobe in 4 studies (Brun et al, 2009; Ecker et al, 2012, 2010b; Ni et al, 2018), and occipital lobe in 4 studies (Brun et al, 2009; Ecker et al, 2012; Ni et al, 2018; Sato et al, 2017). It is unclear if regional white matter volume (WMV) contribute to this overgrowth, with 4 studies reporting regional increases in WMV (Ecker et al, 2010b; Hoeft et al, 2011; Lai et al, 2015; Libero et al, 2016; Xiao et al, 2014), three studies reporting regional decreases in WMV (Hanaie et al, 2016; Lange et al, 2015; Zhou et al, 2014) and a further three studies finding no observable WMV differences (Lin et al, 2015; Ni et al, 2018; Radeloff et al, 2014).…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 96%
“…The "social brain" network has been suggested to be associated with specific social processing tasks, such as face perception [Haxby, Hoffman, & Gobbini, 2000], emotional processing [Calder, Lawrence, & Young, 2001;Rolls, 2004Rolls, , 2008, motor resonance [Rizzolatti, Fogassi, & Gallese, 2001], and theory of mind (ToM, or mentalizing) [Frith & Frith, 2003]. Although the brain regions included in this network are not exactly consistent among different studies, the key regions mainly include the inferior occipital gyrus, posterior fusiform gyrus, middle temporal gyrus (MTG), posterior superior temporal sulcus (pSTS), amygdala, inferior frontal gyrus, and dorsomedial prefrontal cortex [Sato et al, 2017;Williams et al, 2006]. Among these regions of the "social brain" network, numerous alterations of pSTS, which were associated with processing socially relevant stimuli and gaze perception, have been observed in the ASD [Georgescu et al, 2013;Nummenmaa, Engell, von dem Hagen, Henson, & Calder, 2012;von dem Hagen et al, 2011;von dem Hagen, Stoyanova, Rowe, Baron-Cohen, & Calder, 2014].…”
Section: Introductionmentioning
confidence: 99%